Glycerol Hydrogenolysis to Bio-Propanol: Catalytic Activity and Kinetic Model for Ni/C Modified with Al(H₂PO₄)₃ - Gatti, Martín Nicolás (2023)
The aim of the present research is to investigate the effect of different operation variables in the hydrogenolysis of glycerol to 1-propanol and to develop a simple kinetic model useful for the design of the reactor. For this purpose, a carbon-based composite was impregnated with 4 wt.% of Al(H₂PO₄)₃ (CPAl) and used as a support to prepare a Ni catalyst. The support and the catalyst were characterized by BET, XRD, NMR, potentiometric titration, isopropanol decomposition reaction, TEM and TPR analysis. The catalytic tests were carried out at 220–260 °C and 0.5–4 MPa of H₂ initial pressure varying the glycerol concentration in aqueous solutions between 30 and 80 wt.%. The presence of aluminum phosphates in the Ni/CPAl catalyst moderates the surface acidity and the formation of Ni₂P leads to a high selectivity towards 1-propanol. In this sense, the Ni/CPAl catalyst showed total glycerol conversion and 74% selectivity towards 1-propanol at 260 °C and 2 MPa of H₂ initial pressure using 30 wt.% glycerol aqueous solution and 8 h of reaction time. A slight increase in particle size from 10 to 12 nm was observed after a first reaction cycle, but no changes in acidity and structure were observed. Based on these results, a power-law kinetic model was proposed. For glycerol consumption, partial orders of 0.07, 0.68 and −0.98 were determined with respect to glycerol, H₂ and water, and an apparent activation energy of 89 kJ mol⁻¹ was estimated. The results obtained indicate that the model fits the experimental concentration values well and can predict them with an average error of less than 7%.